Byaṅ gter Spyan-ras-gzigs kyi bkaʼ sruṅ mchod thabs bźugs so - Rgod-kyi-ldem-ʼphru-can, Gter-ston, 1337-1408 (s.n., 1977)
Liturgical text for the propitation of the protective deities of the Avalokiteshvara cycle of practice of the Changter revelations of the Nyingmapa.